Demographic factors affecting secondary mathematics teachers’ conceptions of assessment / Bibi Mahdieh Mirian - Bibi Mahdieh , Mirian (2019)
Assessment of student learning is a vital step in the mathematics teaching and learning process. Data obtained from assessments enable teachers to reflect on and make improvements to their practice. This single embedded quantitative study explores teachers’ conception in the context of a new mathematics curriculum in Iran where major educational reform has been undertaken. Thus, the main purpose of this study was to investigate in-service Iranian mathematics teachers’ conception of assessment at three grades of lower secondary school 7th, 8th ,9th in seven educational districts in Mashhad, one of the cities in the North East of Iran. In addition, to determining whether there are differences in teachers’ conceptions of assessments according to three demographic characteristics of mathematics teachers such as years of experience, educational qualifications and gender. There were 352 mathematics teachers included in the study. The instrument used to conduct this study was the Teachers’ Conceptions of Assessment III Abridged (COA-III, Brown 2006) which had 27 items. The findings of Multivariate Analysis of Variance (MANOVA) indicated that the highest level of agreement among mathematics teachers was student and school accountability purpose of assessment. The only significant differences were noted between educational qualifications and teachers’ conception of assessment. The findings of this study contribute to the area of mathematics teachers’ conception and assessment in Iran after the reform movement in the mathematics curricula. Besides, the findings suggested that professional development needs to be provided for teachers in order for teachers’ conception to be compatible with the ideas in the proposed mathematics curriculum reform.